2005
DOI: 10.1007/bf02849884
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of acute adult poisoning in a 6-year period and factors affecting the hospital stay

Abstract: Case management of adult patients with acute poisoning in a university-based emergency department to determine the factors that affect duration of hospital stay was assessed. In this survey, data were obtained for the period between January 1, 1997 and December 31, 2002 at the emergency department (ED). Case analyses of 2229 patients older than 14 years of age were reviewed. Of all patients, 725 (32.5%) were male, 801 (35.9%) were younger than 20, and 540 (24.2%) were older than 30 years. Mean ages of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
49
3
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 19 publications
11
49
3
5
Order By: Relevance
“…9 Another study by Satar et al confirmed the same gender distribution data. 13 Our age groups are similar to these studies.…”
Section: Discussionsupporting
confidence: 90%
“…9 Another study by Satar et al confirmed the same gender distribution data. 13 Our age groups are similar to these studies.…”
Section: Discussionsupporting
confidence: 90%
“…[4] Suicide attempts using calcium channel antagonists shows a significantly higher mortality. [5,6] Increasing elder population in Turkey, increased the number of patients using cardiovascular drugs. Hence, the need exists for studies regarding the incidence and features of cardiovascular drug toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Metal phosphide compounds are widely used as rodenticides and insecticides in Turkey (2). AP is manufactured in the solid form and is stored as packed huge tablets and granules.…”
Section: Discussionmentioning
confidence: 99%